OPTIMASI PEMANFAATAN IRIGASI SUMUR POMPA (STUDI KASUS PADA SUMUR POMPA DI DESA WATULAWU KECAMATAN PONDIDAHA) - Erawan, Dedi (Jurnal Agroteknos, 2011)
ABSTRACTThe operation of groundwater irrigation requires additional cost for fuel and pump operators.    This,  therefore, require  careful cost  calculation in  order  to  obtain expected income.  For this purpose, the research was conducted to optimize the usage of irrigation water from one of wells at Watulawu, Pondidaha, to determine the most profitable crop species and cropping system.  The optimization was conducted using a linier program with QSB (Quantitative System Business) software, with the objective function was the maximum profit  of  farming  and  the  limiting  function  was  the  availability of  irrigation  water  and planting  size.  Out  of  optimized  crop  species  (rice,  maize,  groundnut,  and  soybean), groundnut and rice were the profitable crops.   Planting size for both species was varied during each  planting season, depending on  crop  water requirement and  rainfall.    Early cropping on March required less irrigation water than early cropping on February Keywords : Groundwater irrigation, QBS Software